Analisis Pola Jaringan Komunikasi Pada Pelaksanaan Tradisi Memuja Sebagai Strategi Adaptif Masyarakat Adat Dalam Menghadapi Perubahan Iklim Di Kabupaten Lombok Utara - Paramita, Eka Putri; Suadnya, I Wayan; Riyayanatasya, YY Wima (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
The continuity of traditional practices remains preserved today, especially in North Lombok Regency, NTB. One such tradition is "memuja," held annually by the indigenous community. This tradition aims to maintain water springs and preserve the environment, particularly in response to climate change impacts. Concerns over seasonal anomalies motivate the community to sustain this practice as an adaptive strategy. Understanding communication network patterns in this tradition is crucial, as similar government programs often lack sustainability, unlike memuja, which is voluntarily maintained. This study employs a qualitative descriptive method, with data collected through FGDs and in-depth interviews. The findings indicate: (1) The communication network pattern in memuja is depicted through a sociogram, identifying roles such as opinion leaders, bridges, and isolated individuals, but no liaison officers or cosmopolites were found; (2) Efforts to enhance community understanding of climate change as an adaptive strategy through memuja include climate literacy, attitudes, self-efficacy, and environmental behaviors. This tradition represents a vital adaptation strategy in addressing climate change challenges.